Penerapan Media Game Wordwall Model TGT untuk Meningkatkan Hasil Belajar Perkalian Matematika Kelas IV SDN Sukabumi 2 - Adenita Faradilla; Ribut Prastiwi Sriwijayanti; Ani Anjarwati; Ludfi Arya Wardana (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research is motivated by the low learning outcomes of Mathematics of class IV C students at SDN Sukabumi 2 Kota Probolinggo, especially in understanding the concept of multiplication. Difficulty in memorizing multiplication causes low motivation and student participation. This study aims to improve learning outcomes through educational game media Wordwall with the Teams Games Tournament (TGT) model. The method used is Classroom Action Research (CAR) in two cycles with qualitative and quantitative approaches. The subjects of the study consisted of 23 students. The results showed that in the pre-cycle with a class average of only 60.17%. After the implementation of the Wordwall TGT model, the completion rate increased to 72.82% in cycle I, although it was still below the target of 80%, due to lack of student discipline. In cycle II, the completion rate reached 83.56%, with increased student involvement and discipline in participating in learning. Thus, the implementation of Wordwall with TGT has proven effective in improving the learning outcomes of class IV C students at SDN Sukabumi 2 Kota Probolinggo.